Acute functional deterioration in a child with cerebral palsy. (18th December 2012) - Smyth, Elizabeth; Kaliaperumal, Chandrasekaran; Leonard, Jane; Caird, John
Abstract : We describe a case of acute functional deterioration in a 13-year-old girl with severe spastic diplegia (GMFCS III) and a new diagnosis of diffuse intrinsic pontine glioma (DIPG). She presented with acute deterioration in mobility and motor function over 1 month, which was associated with dysarthria, dysphagia and behavioural change. Her mother had noticed subtle functional deterioration over the 2 months prior to this. Her physiotherapist who was concerned about her acute functional deterioration referred her for emergency review. Neurological imaging revealed a diffuse pontine lesion consistent with DIPG. She was subsequently referred to oncology. She deteriorated further, clinically, over the next few days and following discussion with the team; her family opted for palliative treatment, given the poor prognosis associated with DIPG.